CORRELATION BETWEEN BODY ADIPOSITY INDEX, BODY MASS INDEX AND ESTIMATED BODY FAT BY SKINFOLD THICKNESS IN DIFFERENT AGE GROUPS (Fiep Bulletin - online, 2012)
Obesity is a known public health problem. The evaluation of the individual is paramount, so you can diagnose obesity and overweight, and BMI and skinfold measurement are widely used in clinics, academies and scientific studies. Bergman et al. (2011) present the Body Adiposity Index (BAI), in order to estimate the percentage of body fat, using only the measurements of hip circumference and height. This index is presented also as an alternative method to the Body Mass Index (BMI) in the identification of obesity. Sulino et al. (2011) show the correlation between BMI and the BAI, finding a high correlation between the two methods, which enables the use of BAI as a tool for the diagnosis of body fat. Thus, this study shows a correlation between the IAC, BMI and skinfold method in order to identify the feasibility of using BAI in different age groups. The study included 96 individuals classified as sedentary, 48 females with body mass 66.74 ± 11.38 kg and height of 161.51 ± 5.74 cm, and 48 males with body mass of 82.73 ± 12.04 kg and height of 174.16 ± 7.19 cm, aged between 20 and 60 years old, divided by age groups. As a result, we identified a high correlation between BAI and skinfolds at all ages, both men and women, while for women aged 41 to 60 years, BMI has shown a higher correlation, possibly due to a better applicability of BMI in this age group. From the results presented, we can conclude that, for the sample, the BAI is presented as a viable alternative for the diagnosis of body fat.
Keywords: correlation; body fat; physical assessment